Science Teaching Materials for Students with Special Needs: Concept of Exhaust Emissions in Transportation Equipment (Unijourn Publisher, 2021)
The purpose of this study was to find out science learning materials for students with special needs regarding the concept of exhaust emissions in transportation equipment. The research method used experimental demonstration. We prepared research instruments for learning the concept of exhaust emissions in transportation equipment for students with special needs. The results showed that several tools and materials must be provided and several lists of research instrument questions were made. In addition to tools and materials, methods and media must also be adapted to the needs of the child. That’s because the methods and media that are in accordance with the needs of students can make it easier for students to understand the learning material. We hope that the results of this study can make it easier for teachers to teach the concept of exhaust gas emission on transportation equipment, especially for students with special needs.